Megasports events as an instrument for development adaptive (in focus of the XVIII Deaflympic winter games - 2015) - E. A. Gureeva; T. A. Zaikina (Путеводитель предпринимателя, 2020)
Nowadays the problems of disabled people and disability are one of the most important government problems, because this problem concerns a large number of people with disability. Disability is a social phenomenon that no country can avoid. One of the most essential directions of disabled people integration in our society and their successful physical recovery are physical culture and sport. It is just as important as rehabilitation with the help of education and work. Physical culture and sport for disabled are generally considered to be not only a method of physical rehabilitation, but also a method of social rehabilitation (social activity and personal achievements) - a permanentform of vital energy. The basic instruments ofdevelopment ofadaptive sports are examined in this article. Special attention is paid to sport events, particularly to the XVIII Deaflympic Winter Games, which were held in Hanty-Mansiysk, Russia in 2015.